Golda Meir : Israel's matriarch - Lipstadt, Deborah E. (Jewish lives., 2023)
"In tracing the life of Golda Meir, Deborah E. Lipstadt explores the history of the Yishuv and Jewish state from the 1920s through the 1973 Yom Kippur War, all while highlighting the contradictions and complexities of a person who was only the third woman to serve as a head of state in the twentieth century."--